A flexible online apparatus for projectile launch experiments - Paiva, Carlos (2014)
In order to provide a more flexible learning environment in physics, the developed projectile launch apparatus enables students to determine the acceleration of gravity and the dependence of a set of parameters in the projectile movement. This apparatus is remotely operated and accessed via web, by first scheduling an access time slot. This machine has a number of configuration parameters that support different learning scenarios with different complexities.